Bimodalne transportne tehnologije - faktor povezivanja Jugoslavije i EZ - Ivaković, Čedomir (Promet - Traffic&Transportation, 2012)
This paper deals with different methods of bi-modal transport technology as well as the possibility of their application. The concept and term of bi-modal technology has been defined, respective advantages and disadvantages have been reviewed and a comparison drawn as to their economical aspect based upon respective data for piggy-back transport.